Peranan Guru Sejarah dalam Pemahaman Wawasan Kebangsaan pada Siswa Kelas XI IPS 1 SMA Negeri 12 Sijunjung - Juli Adek Klismen; Kaksim Kaksim; Meldawati Meldawati (Horizon, 2021)
Instilling national values in schools is one of the efforts to shape student into citizens with character, because education can prepare the youger generation to play a role in the life of the nation in the future. However, in reality, students are still found in schools who do not understand ther country and nation. Thmselves and lack discipline. Phenomena that occur in schools, are still found by students who are late for the ceremony. National insight becomes important to be delevoped, because the sense of nationality as a manifestation of a sense of love for the homeland, in turn raises our awareness of the value and value of a sense of unity and nationality. So the conclusion that the researcher can convey  is that the role of the history teache understanding national insightis very important and the history teacher can explain to students in clas XI IPS 1, and the role of the teacher is clearly visible after the researcher conducted interviews with students with a lot of knowledge about it, so the final conclusion that researchers got was that the role of history teachers was important in understanding national insight